Initial experience of cardiac multidetector-row CT using a multisector reconstruction algorithm: studies of normal volunteers - Horiguchi, J; Nakanishi, T; Ito, K; Shen, Y (Nihon Igaku Hoshasen Gakkai zasshi. Nippon acta radiologica, 2000)
Multisector reconstruction is a newly devised algorithm that realizes cardiac images of high temporal resolution (0.13 msec minimum) at arbitrary phases of the cardiac cycle without degrading the signal-to-noise ratio. In this study, we examined the image quality of volunteers' examinations. Multisector reconstruction was found to be a feasible tool, providing excellent cardiac images almost without motion artifact. In addition to detecting coronary calcium, with the advantage of multidetector-row CT for good z-axis resolution and for volumetric data acquisition of the entire heart within a single breath hold, this technique could provide 3D images beneficial to the analysis of cardiac motion.